(untitled) (Research, Society and Development, 2020)
The objective of this work was to analyze the content of bioactive compounds extracted from the carrot, through an experimental design of 3 factors, 3 levels and two axial points, including extraction time (17-37-57min), temperature (30-50-70ºC) and ethanol concentration (50-65-80%). The result was expressed as a percentage. Based on the results, it can be said that time did not significantly influence the extraction of antioxidant compounds (p> 0.001), and that the temperature is directly proportional to the yield. Regarding phenolic compounds, only temperature was significant, and for flavonols, only time and proportion. The use of ethanol as a solvent showed good results when compared to the commonly used solvents, in addition to having the quality of being economically viable and food grade. Another important factor was the pre-treatment of the sample, which allowed good yield values ​​when compared to the literature.